CBT COMPETENCE IN NOVICE THERAPISTS IMPROVES ANXIETY OUTCOMES. Issue 2 (5th December 2012) - Brown, Lily A.; Craske, Michelle G.; Glenn, Daniel E.; Stein, Murray B.; Sullivan, Greer; Sherbourne, Cathy; Bystritsky, Alexander; Welch, Stacy S.; Campbell‐Sills, Laura; Lang, Ariel; Roy‐Byrne, Peter; Rose, Raphael D.
<x xml:space="preserve">Abstract</x> Objective This study explores the relationships between therapist variables (cognitive behavioral therapy [CBT] competence, and CBT adherence) and clinical outcomes of computer‐assisted CBT for anxiety disorders delivered by novice therapists in a primary care setting. Methods Participants were recruited for a randomized controlled trial of evidence‐based treatment, including computer‐assisted CBT, versus treatment as usual. Therapists (anxiety clinical specialists; ACSs) were nonexpert clinicians, many of whom had no prior experience in delivering psychotherapy (and in particular, very little experience with CBT). Trained raters reviewed randomly selected treatment sessions from 176 participants and rated therapists on measures of CBT competence and CBT adherence. Patients were assessed at baseline and at 6‐, 12‐, and 18‐month follow‐ups on measures of anxiety, depression, and functioning, and an average Reliable Change Index was calculated as a composite measure of outcome. CBT competence and CBT adherence were entered as predictors of outcome, after controlling for baseline covariates. Results Higher CBT competence was associated with better clinical outcomes whereas CBT adherence was not. Also, CBT competence was inversely correlated with years of clinical experience and trended (not significantly, though) down as the study progressed. CBT adherence was inversely correlated with therapist tenure in the study. Conclusions Therapist competence was related to improved clinical outcomes when CBT for anxiety disorders was delivered by novice clinicians with technology assistance. The results highlight the value of the initial training for novice therapists as well as booster training to limit declines in therapist adherence.